Antecedents of organizational citizenship behavior and the mediating effect of organization commitment in the hotel industry - Jue, Xin Tan; Tat, Huei Cham; Zawawi, Dahlia; Abdul Aziz, Yuhanis (MAG Scholar, 2019)
The rapid growth of the hotel industry in the current era of globalization requires hotel operators to acknowledge the importance of service provision and its management in order to compete effectively and to gain competitive advantage at the same time. Building a strong workforce is essential to realize this vision. Therefore, it is vital for the hotel operators to establish a good relationship between their management and the employees to achieve its goals and objectives. As such, this paper aims to examine the importance of emotional intelligence in shaping benevolent leaders and organizational commitment as the mediator of the relationship between benevolent leadership and organizational citizenship behavior. This study is one of the pioneer studies of benevolent leadership conducted in a multicultural context. Moreover, this study also highlighted the effectiveness of benevolent leadership in encouraging voluntary extrarole effort and improving the turnover issues in the hotel industry of Malaysia. The data was collected using multistage sampling from 300 hotel employees from fourand five-star hotels in Klang Valley of Malaysia. Both Statistical Package for the Social Sciences (SPSS) and AMOS (Analysis of Moment Structures) statistical software were used for the hypotheses testing. The results from the analysis showed that the emotional intelligence of supervisors is significantly related to benevolent leadership. Organizational commitment was found to have a mediation effect on the relationship between benevolent leadership and organizational citizenship behavior.